Analysis of Spatial Working Memory Using the Y-Maze on Rodents Treated with High-Calorie Diet and Moderate-Intensity Exercise - Melbiarta, Rezy Ramawan; Kalanjati, Viskasari P.; Herawati, Lilik; Salim, Yusuf; Othman, Zulhabri (Folia Medica Indonesiana, 2022)
Highlights: • This article reports the use of the Y-maze as a simple yet effective method to measure spatial working memory in mice. • The Y-maze method can be used safely without exposing the animals to additional stressors, as evidenced by the absence of mortality following the test. Abstract: Spatial working memory (SWM) in humans and animal models with impaired cognitive functions has been analyzed through a number of methods. However, this is still understudied in animal models treated with a high-calorie diet (HCD) and moderate-intensity exercise (MIE). The Y-maze was utilized as the assessment method in this study. A 40 x 9 x 9 cm3 Y-maze was employed to observe the animal models' spontaneous alternation (SA) as the representation of their SWM. This was done by calculating the total alternation percentage divided by total entry minus two. A total of 17 female Mus musculus mice aged 8 weeks were tested in the Y-maze to investigate their SWM using SA calculations. Each mouse was analyzed for eight minutes and recorded in a dark and quiet room to minimize bias due to environmental noise and lighting. Comparing the treatment group's (HCD+MIE) SA to the control group's SA revealed no statistically significant difference (p=0.451). Seven mice in the treatment group performed similarly to the mice in the control group in the Y-maze test, with no significant difference in their ability to complete the task. The mice in the treatment group exhibited no motor impairment, as indicated by complete movements of all their extremities while exploring the Y-maze within the allotted time. In conclusion, the Y-maze can be used as a reliable method to analyze SWM in overweight/obese Mus musculus animal models treated with moderate-intensity physical exercise.